Characteristics of Microseismic Generated During Shear Failure of Granite With Structural Plane of Various Connectivities - Xianzhe Liang; Zhicheng Hu; Xiufen Qin; Yaoqun Deng; Jianqing Jiang; Guoshao Su (Advances in Civil Engineering)
The structural plane significantly changes the rock failure behavior. The connectivity of the structural plane generally varies for the rocks in different engineering practices or rock environments. In this manuscript, a series of direct shear tests on granite specimens are carried out using the true-triaxial testing machine. Structural planes with different lengths are cut in the granite specimen to simulate the different connectivity degrees of structural planes. The microseismic (MS) generated from the stressed specimen under direct shear loading conditions is monitored during testing. Then, the characteristics of the obtained MS are systematically investigated. The experimental results indicate that the structural plane connectivity exhibits a significant effect on the characteristics of MS generated during the shear failure of granite. With the increase of the structural plane connectivity, the time for the first rise of the MS active index is advanced, and the final value of the accumulated MS active index decreases. A frequency division phenomenon can be found during the evolution of the MS main frequency; with the increasing structural plane connectivity, the frequency division becomes less pronounced. Also, it can be found that in the middle-to-late stages of the tests, the b value initially drops to a very low level and then rises back to the original level; before rock failure, the b value continuously decreases at a swift rate, but the average rate of decrease increases with the increase in structural plane connectivity. The evolution patterns of high-amplitude MS events in the time–frequency domain are the same, initially concentrated in the low-frequency region during the mid-term of the test and then dispersed into various frequency bands approaching macroscopic rock shear failure; however, the duration of the high-energy region is negatively correlated with the structural interface connectivity. The fractal dimension exhibits a rapid increase before the overall rock shear failure; the rate of increase in the fractal dimension approaching macroscopic failure decreases with the increased structural interface connectivity. The experimental results obtained in this manuscript can provide valuable insights into the mechanism of rock shear failure and the prediction of the engineering disaster induced by rock shear failure.